"A great caravansary filled with strangers": American popular democracy in T. C. Haliburton's political satire. (September 2016) - Godeanu-Kenworthy, Oana
This article examines the political satire of Nova Scotian writer and politician Thomas Chandler Haliburton through the lens of early nineteenth-century transatlantic debates over reform and the best form of government. Haliburton's Sam Slick sketches, featuring a charismatic Yankee commenting on global political affairs, were immensely popular at the time, being published and read in Britain, Canada, and the US. The following pages argue that Haliburton's portrayal of American culture is informed by his negative views on popular democracy and on its relationship with the nascent industrial capitalism transforming North America. Haliburton's political satire was meant to persuade colonial readers that the introduction of American-style elective institutions in Nova Scotia had the potential to radically alter British North American culture, and push the colonies out of the orbit of the Empire.